Efektivitas Penerapan Strategi Pembelajaran Peningkatan Kemampuan Berfikir Dalam Meningkatkan Berfikir Kritis Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Jannatul Magfiroh; Ais Kamila Putri; Arofik Arofik; Iswatun Hasanah; Amna Amna (Kariman: Jurnal Pendidikan Keislaman, 2024)
The effectiveness of implementing learning strategies to improve students' critical thinking skills in Islamic Religious Education at Al-Muarraf Bicorong Junior High School (SMP), aims to determine the effectiveness of implementing learning strategies to improve students' critical thinking skills and to determine the improvement of students' critical thinking skills in Islamic Religious Education. This study addresses two key issues: first, how effective is the implementation of learning strategies to improve students' critical thinking skills in Islamic Religious Education at Al-Muarraf Bicorong Junior High School (SMP), Pakong, Pamekasan? Second, the supporting and inhibiting factors in using learning strategies to improve students' critical thinking skills in Islamic Religious Education. This study employed a descriptive qualitative approach, with the results obtained in the form of descriptive data. The data sources were the principal, Islamic Religious Education teachers, and students. Data analysis was conducted using descriptive qualitative methods, including data reduction and presentation. The results of the research that the researcher has conducted are found that first, the strategy is effective because students can explain with students' understanding according to their own experiences and can express their opinions freely so that the class situation becomes effective and conducive, in following Islamic Religious Education learning students do not feel bored and are better able to understand the theory conveyed by the teacher. Second, supporting factors include, the willingness and curiosity of students in following learning, and the enthusiasm of students in learning and the mastery of teachers in managing the class so that it runs conducively. Meanwhile, the inhibiting factors in the use of learning strategies to improve thinking skills are the lack of awareness of students about the importance of formal education, the state of students who are tired or sleepy, and the lack of self-confidence of students.